2012
DOI: 10.5402/2012/168264
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Neuropathy Measured by Heart Rate Variability and Markers of Subclinical Atherosclerosis in Early Type 2 Diabetes

Abstract: Cardiac autonomic neuropathy (CAN) is a critical complication of type 2 diabetes mellitus (T2DM). Heart rate variability (HRV) is a noninvasive tool to assess cardiac autonomic function. We aimed to evaluate whether CAN is associated with increased risk of atherosclerosis in T2DM. A total of 57 diabetic and 54 nondiabetic subjects, free of coronary heart disease, were recruited. Carotid intima media thickness (CIMT), coronary calcium score (CAC), and brachial Flow Mediated Dilation (FMD) were measured. Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…(Tsuji et al, 1996) Studies by our laboratory and others have investigated the correlation between HRV and hypertension, cholesterol, gender, age, hyperglycemia and diabetes, smoking, body mass index, oxidative stress and heart disease. (Da Silva et al, 2004; Lampert et al, 2008; McLachlan et al, 2010; Tacoy et al, 2010; Thayer et al, 2010; Johnson et al, 2011; Khandoker et al, 2011; Kotecha et al, 2011; Fakhrzadeh et al, 2012; Matthews et al, 2012; Thiyagarajan et al, 2013) However, these studies did not stratify the cohorts according to the FRS but rather evaluated the magnitude of the HRV associated with presence or absence of the pathology being investigated. Hillebrand et al (2013) recently reported that HRV is a useful marker for incidence of CVD in a population without any signs of CVD based on lowered time domain HRV values (Hillebrand et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(Tsuji et al, 1996) Studies by our laboratory and others have investigated the correlation between HRV and hypertension, cholesterol, gender, age, hyperglycemia and diabetes, smoking, body mass index, oxidative stress and heart disease. (Da Silva et al, 2004; Lampert et al, 2008; McLachlan et al, 2010; Tacoy et al, 2010; Thayer et al, 2010; Johnson et al, 2011; Khandoker et al, 2011; Kotecha et al, 2011; Fakhrzadeh et al, 2012; Matthews et al, 2012; Thiyagarajan et al, 2013) However, these studies did not stratify the cohorts according to the FRS but rather evaluated the magnitude of the HRV associated with presence or absence of the pathology being investigated. Hillebrand et al (2013) recently reported that HRV is a useful marker for incidence of CVD in a population without any signs of CVD based on lowered time domain HRV values (Hillebrand et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This may have clinical relevance because alterations of cardiovascular variability have been linked to prognosis in coronary patients [41] and have been found to correlate with the degree of coronary stenosis [6,41,42]. Measuring cardiovascular variability could, therefore, help to better identify patients' risk and could favor proper adjustments of their management.…”
Section: Discussionmentioning
confidence: 97%
“…Fisher B.M et.al.in a study seven subjects out 115 asymptomatic diabetic patients showed an abnormal response to 30:15 ratio and in among 9 symptomatic diabetic patients 8 patients have shown abnormal response [18] . Reduction HR response to standing in diabetics and cardiovascular autonomic function was decreased in type-II diabetics because of that severe damage to large myelinated nerve fibers in addition to the widespread neurological degeneration which usually affects the small nerve fibers of the autonomic nervous system was responsible for profound parasympathetic neuropathy in patients with type-2 DM [19].…”
Section: Discussionmentioning
confidence: 99%